Cytomorphology of hepatoblastoma with histological correlation and role of SALL4 immunocytochemistry in its diagnosis, subtyping, and prognostication. Issue 3 (27th December 2019) - Nakra, Tripti; Roy, Maitrayee; Yadav, Rajni; Agarwala, Sandeep; Jassim, Mohamed; Khanna, Gaurav; Das, Prasenjit; Jain, Deepali; Mathur, Sandeep R.; Iyer, Venkateswaran K.
Abstract : Background: Hepatoblastoma (HB) is the most common malignant pediatric liver tumor, and cytology material is often the only tissue available for evaluation before definitive therapy. Subcategorization of HB based on cytomorphological features thus carries an important role in its prognostication. Spalt‐like transcription factor 4 (SALL4), a marker of embryonic stem cells that is also found in the fetal liver, is reactivated in certain liver tumors. Limited studies have evaluated its role in HB. This study was aimed at evaluating the cytomorphological features of HB and assessing the utility of SALL4 immunocytochemistry (ICC) in its subtyping and prognostication. Methods: Pretherapy fine‐needle aspiration smears from patients diagnosed with HB over a period of 9 years were retrieved. Aspirates were subclassified on the basis of the cytomorphology and were correlated with the histology wherever it was available. ICC for SALL4 was performed in 33 cases, and nuclear staining was considered positive. Results: A total of 53 HB cases were included with 30 available postchemotherapy resection specimens. All the patients were diagnosed as epithelial HB on cytology, and the cases were subclassified as pure fetal (9 of 53), pure embryonal (2 of 53), or combined epithelial HB (42 of 53). There was good concordance between cytology and histology for subtyping. SALL4 immunostaining displayed strong and diffuse nuclear positivity in the embryonal component while focal and weak to negative staining in fetal cells. Conclusions: Fine‐needle aspiration cytology serves as a rapid and effective tool for a correct diagnosis of HB before the implementation of chemotherapy, and SALL4 may serve as a useful diagnostic and prognostic marker. Abstract : Pretherapy subtyping of hepatoblastoma can be effectively performed with fine‐needle aspiration cytology through a detailed cytomorphological evaluation. The differential staining pattern of spalt‐like transcription factor 4 (SALL4) immunocytochemistry aids in the diagnosis by demarcating the embryonal cells from the fetal cells of hepatoblastoma and thus can serve as a useful diagnostic and prognostic marker for hepatoblastoma.